Desórdenes temporomandibulares y trauma - Lutz C, Grettel; Howard M., Madeline (Odovtos - International Journal of Dental Sciences, 2011)
Temporomandibular disorders is a collective term used for different clinical conditions that involve the masticatory muscles, the temporomandibular joint or the associated structures. They are the most common cause of orofacial pain of non-dental origin, their etiology is multifactorial and they have been associated to diverse factors such as depression, stress, anxiety and trauma. Trauma, from a psychological perspective, is a perceptual and direct experience that develops in relation to one of the following events: experience or witnessed threatened death or serious injury, or other threat to the physical integrity or learning about unexpected or violent death, serious harm, or threat of death or injury experienced by a family member or other significant person. This article explores the relationship within temporomandibular disorders, traumatic experiences and their psychopathophysiological impact.